2011
DOI: 10.1371/journal.pbio.1001062
|View full text |Cite
|
Sign up to set email alerts
|

Ever-Young Sex Chromosomes in European Tree Frogs

Abstract: Non-recombining sex chromosomes are expected to undergo evolutionary decay, ending up genetically degenerated, as has happened in birds and mammals. Why are then sex chromosomes so often homomorphic in cold-blooded vertebrates? One possible explanation is a high rate of turnover events, replacing master sex-determining genes by new ones on other chromosomes. An alternative is that X-Y similarity is maintained by occasional recombination events, occurring in sex-reversed XY females. Based on mitochondrial and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 50 publications
(64 reference statements)
4
202
0
2
Order By: Relevance
“…Of course, sex determination mechanisms are also intricate in fishes, because fishes, like other aquatic animals of amphibians and reptiles, include male or female heterogametic genetic sex determination with or without strongly differentiated sex chromosomes [88,89]. A recent report indicates that sex-chromosome homomorphy in European tree frogs does not result from a recent turnover but is maintained over evolutionary timescales by occasional X-Y recombination, implicating that seemingly ever-young sex chromosomes may thus carry old-established sex-determining genes [90]. Moreover, B chromosomes in addition to standard chromosomes are also found to have a functional effect on sex determination in one cichlid species (Lithochromis rubripinnis) from Lake Victoria [91], which implies that a portion of sex chromosomes has been derived from B chromosomes.…”
Section: Sex Determination and Candidate Sex Determination Genesmentioning
confidence: 99%
“…Of course, sex determination mechanisms are also intricate in fishes, because fishes, like other aquatic animals of amphibians and reptiles, include male or female heterogametic genetic sex determination with or without strongly differentiated sex chromosomes [88,89]. A recent report indicates that sex-chromosome homomorphy in European tree frogs does not result from a recent turnover but is maintained over evolutionary timescales by occasional X-Y recombination, implicating that seemingly ever-young sex chromosomes may thus carry old-established sex-determining genes [90]. Moreover, B chromosomes in addition to standard chromosomes are also found to have a functional effect on sex determination in one cichlid species (Lithochromis rubripinnis) from Lake Victoria [91], which implies that a portion of sex chromosomes has been derived from B chromosomes.…”
Section: Sex Determination and Candidate Sex Determination Genesmentioning
confidence: 99%
“…Previous work on this species has shown that its sex determination system is at least 5 million years old, but that occasional X-Y recombination prevents degeneration of the Y chromosome (Stöck et al, 2011). The sex chromosome is largely homologous to chromosome 1 in Xenopus tropicalis, and contains the candidate sex determination gene Dmrt1 (Brelsford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Homomorphy may result from occasional X-Y recombination and/or frequent sex-chromosome turnovers (see, for example, Stöck et al, 2011;Dufresnes et al, 2015), two mechanisms possibly driven by incomplete genetic control over sex determination (Perrin, 2009;Grossen et al, 2011). Sexdetermination systems seem particularly labile in Ranidae, where sex chromosomes may differ between closely related species or even conspecific populations (Nishioka and Sumida, 1994;Miura, 2007).…”
Section: Introductionmentioning
confidence: 99%